DIELECTRIC PROPERTIES OF RED BLOOD CORPUSCLES OF WORKERS CHRONICALLY EXPOSED TO BENZENE IN WORKPLACE - MA, Kotb; HS, Ramadan; El Din R, Shams; HA, Motaweh; EA, El-Bassiouni (European Scientific Journal, ESJ, 2014)
Studying the dielectric properties of cells and of structural parts of the cell (membrane, cytoplasm, etc.) is an important way to obtain valuable information about cell structures and their functions and metabolic mechanisms. In this work, the RBCs human blood of control and benzene exposed workers were separated by centrifugation and washed with phosphate buffer and adjusted to pH = 7.4, 290+ 3 mOsm/Kg and 50% hematocrit value. The relative permittivity ε’, dielectric loss ε", dielectric strength Δε’, relaxation time τ and the ac conductivity σ a-cof these cells were studied using an a-c voltage in the frequency range 50Hz -1MHz. The results obtained indicate that all the studied electric parameters, including real conductivity, real and imaginary relative permittivity in addition to the relaxation time, dielectric loss and the dissipation factor suffered significant changes in the RBCs of the benzene exposed workers than that of the control subjects.